Elderly smallholder farmers' perceptions of and adaptation to climate variability and change in rural Ghana. Issue 2 (25th November 2021) - Appiah, Divine Odame; Asante, Felix; Antwi-Boadi, Lois; Serbeh, Richard
Abstract : Purpose: This paper aims to examine elderly smallholder farmers' perceptions of and adaptation to climate variability and change in the Offinso Municipality, Ghana. Design/methodology/approach: This paper used quantitative and qualitative methods. Quantitative data were analyzed with frequencies and chi-square tests, whereas qualitative data were thematically analyzed. Findings: The results showed that elderly smallholder farmers' knowledge of climate variability and climate change were based on their sex, level of formal education and experience in farming. Elderly smallholder farmers adopted both on-farm and off-farm strategies to cope with climate change and variability. The vulnerability of elderly smallholder farmers to climate change calls for social protection mechanisms such as a pension scheme that guarantees access to monthly cash transfers. Such a scheme will ease constraints to livelihood and ensure improved well-being. Originality/value: Elderly smallholder farmers have remained invisible in discourses on perceptions and adaptation to climate change despite the surge in number of this category of farmers. This paper therefore represents an attempt to highlight the experiences of elderly smallholder farmers with climate variability and change.